Quality Standards in e-Learning: A matrix of analysis - Frydenberg, Jia (International Review of Research in Open and Distributed Learning, 2002)
Most institutions of postsecondary and higher education are creating or adopting quality statements, standards, and criteria regarding their niche of the “eLearning enterprise.” In doing so, they have a tendency to reinvent the wheel. This article summarizes current published quality standards in the US, and analyzes and organizes them into a nine-cell matrix. It concludes with discussion of emerging issues with respect to the nine standards-areas.